A geothermal energy system for wastewater sludge drying and electricity production in a small island. (15th November 2018) - Calise, F.; Di Fraia, S.; Macaluso, A.; Massarotti, N.; Vanoli, L.
Abstract: Waste management and energy production are becoming critical issues in geographically disadvantaged areas, like small islands. For waste disposal the most common strategy is shipping to the mainland, due to the scarcity of land and local suitable treatments. Electricity generation is based on the importation of fossil fuels for local production, due to the lack of connections with continental energy networks. Both, waste shipping and fuels importation determine strong dependence on the mainland, as well as high economic and environmental cost for small islands. Therefore, using local renewable energy sources is extremely attracting. In this work, geothermal energy is considered for thermal drying of wastewater sludge and electricity supply of the whole wastewater treatment. The system is analysed for the case study of Pantelleria, a small island in Southern Italy, where sludge is currently dewatered to a final water content of 70–80%, and then shipped to mainland. The proposed system decreases wastewater sludge to be transported and disposed by 73.3%. Its profitability is demonstrated by several economic indicators, showing a Simple Payback time equal to 8.34 years and a Net Present Value of 502 k€. In addition, a sensitivity analysis for the main parameters affecting plant operation is carried out. Highlights: A geothermal system for sewage sludge drying and electricity production is proposed. Energy, environmental and economic analysis is carried out for a real case study. Electricity produced supplies the proposed system and the upstream wastewater plant. The system reduces wastewater sludge to be disposed by 73.3%.